Skeletal muscle mitochondrial H2O2 emission increases with immobilization and decreases after aerobic training in young and older men - Gram, Martin; Vigelsø, Andreas; Yokota, Takashi; Helge, Jørn Wulff; Dela, Flemming; Hey‐Mogensen, Martin (The Journal of physiology, 2015)
Key points Currently, it is not known whether impaired mitochondrial function contributes to human ageing or whether potential impairments in mitochondrial function with age are secondary to physical inactivity. The present study investigated mitochondrial respiratory function and reactive oxygen species emission at a predefined membrane potential in young and older men subjected to 2 weeks of one‐leg immobilization followed by 6 weeks of aerobic cycle training. Immobilization increased reactive oxygen species emission and decreased ATP generating respiration. Subsequent aerobic training reversed these effects. By contrast, age had no effect on the measured variables. The results of the present study support the notion that increased mitochondrial reactive oxygen species production mediates the detrimental effects seen after physical inactivity and that ageing per se does not cause mitochondrial dysfunction. Mitochondrial dysfunction, defined as increased oxidative stress and lower capacity for energy production, may be seen with ageing and may cause frailty, or it could be that it is secondary to physical inactivity. We studied the effect of 2 weeks of one‐leg immobilization followed by 6 weeks of supervised cycle training on mitochondrial function in 17 young (mean ± SEM: 23 ± 1 years) and 15 older (68 ± 1 years) healthy men. Submaximal H2O2 emission and respiration were measured simultaneously at a predefined membrane potential in isolated mitochondria from skeletal muscle using two protocols: pyruvate + malate (PM) and succinate + rotenone (SR). This allowed measurement of leak and ATP generating respiration from which the coupling efficiency can be calculated. The protein content of the anti‐oxidants manganese superoxide dismuthase (MnSOD), CuZn superoxide dismuthase, catalase and gluthathione peroxidase 1 was measured by western blotting. Immobilization decreased ATP generating respiration using PM and increased H2O2 emission using both PM and SR similarly in young and older men. Both were restored to baseline after the training period. Furthermore, MnSOD and catalase content increased with endurance training. The young men had a higher leak respiration at inclusion using PM and a higher membrane potential in State 3 using both substrate combinations. Collectively, the findings of the present study support the notion that increased mitochondrial reactive oxygen species mediates the detrimental effects seen after physical inactivity. Age, on the other hand, was not associated with impairments in anti‐oxidant protein levels, mitochondrial respiration or H2O2 emission using either protocol.